2015
DOI: 10.3389/fpls.2015.01076
|View full text |Cite
|
Sign up to set email alerts
|

Functional Divergence of APETALA1 and FRUITFULL is due to Changes in both Regulation and Coding Sequence

Abstract: Gene duplications are prevalent in plants, and functional divergence subsequent to duplication may be linked with the occurrence of novel phenotypes in plant evolution. Here, we examine the functional divergence of Arabidopsis thaliana APETALA1 (AP1) and FRUITFULL (FUL), which arose via a duplication correlated with the origin of the core eudicots. Both AP1 and FUL play a role in floral meristem identity, but AP1 is required for the formation of sepals and petals whereas FUL is involved in cauline leaf and fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 65 publications
0
24
0
1
Order By: Relevance
“…Makova et al (2003) uncovered that nonsynonymous (Ka) and synonymous (Ks) substitution rates were significantly correlated with gene expression divergences of human duplicate genes at early stages after duplication [ 50 ]. McCarthy et al (2015) reported that the functional divergence between two Arabidopsis paralogous genes is attributable to both regulation and changes in coding sequence [ 52 ]. In our study, we examined whether two genes with high similarity in coding sequences shared high similarity in gene expression patterns across different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Makova et al (2003) uncovered that nonsynonymous (Ka) and synonymous (Ks) substitution rates were significantly correlated with gene expression divergences of human duplicate genes at early stages after duplication [ 50 ]. McCarthy et al (2015) reported that the functional divergence between two Arabidopsis paralogous genes is attributable to both regulation and changes in coding sequence [ 52 ]. In our study, we examined whether two genes with high similarity in coding sequences shared high similarity in gene expression patterns across different tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Petunia AP1/SQUA Family Members Function in a Largely Redundant Fashion and Are Required for IM Identity Different members of the AP1/SQUA subfamily in Arabidopsis have evolved unique roles during development as exemplified by the distinct phenotypes of the single ap1 and ful mutants. Swapping experiments suggest that functional divergence between AP1 and FUL is due to changes in both expression pattern and coding sequence (McCarthy et al, 2015). At the same time, AP1, CAL, and FUL have retained a redundant function in inflorescence architecture (Ferrándiz et al, 2000), whereas CAL shares a cryptic role in petal development redundantly with AP1 (Castillejo et al, 2005).…”
Section: Implication Of Sep and Agl6 Gene Functions In Floral Organ Imentioning
confidence: 99%
“…There is a large body of experimental evidence demonstrating how biological process functions differ between two plant duplicates. For example, paralogous MADS domain transcription factors control different aspects of plant development, and this functional divergence is due to changes in both promoter and coding regions (McCarthy et al, 2015). To summarize how the biological processes involving duplicates differ from those involving singleton genes, one approach is to examine annotated gene functions.…”
Section: Functions Of Duplicatesmentioning
confidence: 99%